Reactive Power Optimization of Distribution Network Considering the Reactive Power Output of Doubly Fed Induction Generator - Cheng ZHANG; Yu CHEN; Can LI; Liangshuai LU; Zhenglong XIA (南方能源建设)
[Objective] At present, wind power generation has been widely used, but wind power is volatile and unstable, and the grid voltage fluctuation and network loss increase will be caused after wind farms are connected to the grid. To solve these problems, a multi-objective reactive power optimization model of distribution network considering the reactive power output of doubly fed induction generator is proposed. [Method] Based on the segmentation idea, the uncertain dynamic problem of wind power was transformed into a definite static problem, and the improved whale optimization algorithm was used to solve the mathematical model. In order to solve the problems of low precision, slow convergence speed and easy to fall into local optimality of the traditional whale optimization algorithm, a hybrid strategy was adopted to improve whale optimization algorithm, and some improved methods such as tent mapping initialization, adaptive weight and adaptive probability threshold were introduced. [Result] Taking the improved IEEE33 node distribution network as an example, the improved whale optimization algorithm can improve the global search ability and convergence speed comparing the particle swarm optimization and gray wolf optimizer. [Conclusion] The optimal reactive power output of wind farm optimized by the proposed strategy can reduce more system losses and improve the voltage stability of distribution network.